(untitled) (Dhaka University Journal of Science, 2022)
Effects of temperature and solvents on the thermodynamical and electronic properties of N-acetyl-para-aminophenol (APAP) have been investigated using density functional theory (DFT) and time dependent density functional theory (TD-DFT). Calculated results shows that thermodynamic properties such as enthalpy (H), entropy (S) and specific heat capacity (Cv) are increased by the raising of temperature (100 K-1200 K) because of enhancing the intensities of molecular vibration. On the contrary, change of Gibb’s free energy (ΔG) has been decreased with the increase of temperature. FMO energy gap is enlarged by solvation and therefore APAP becomes more stable in solution especially in polar solvents. Moreover, solvation increases the magnitude of ionization potential, electron affinity, electronegativity, chemical potential and global hardness. Two UV absorption maxima (λmax1 and λmax2) are found at 243.08 nm and 193.85 nm which are originated from phenyl and amide chromophore, respectively. The calculated λmax1 and λmax2 agree quite well with the available experimental data. On the other hand, calculated results reveal that solvation blueshifts the electronic absorption spectraas well as enhances the absorption intensity significantly. Dhaka Univ. J. Sci. 69(3): 125-132, 2022 (June)